Tumor Susceptibility Gene 101 Mediates Anoikis Resistance of Metastatic Thyroid Cancer Cells - SAHARAT, KITTIRAT (Cancer Genomics Proteomics, 2018)
Background/Aim: Resistance to anoikis is a pre-requisite step in metastasis, a major cause of death in patients with cancer, including thyroid cancer. Impairing anoikis resistance is a possible strategy for therapy of metastatic cancer. We, therefore, we aimed to investigate the key players of anoikis resistance. Materials and Methods: Papillary-type (BCPAP), follicular-type (FTC133), and anaplastic-type (ARO) thyroid carcinoma cells, cultured in poly(2-hydroxyethyl methacrylate)-coated plates to mimic circulating cells, were used as model systems in this study. Flow cytometry and soft-agar assays were used to determine cells exhibiting anoikis resistance. Proteomics was used to identify candidate proteins and validated using western blot and siRNA knockdown. Results: Only ARO cells showed both anoikis resistance potential and anchorage-independent growth ability. Tumor susceptibility gene 101 protein (TSG101) was identified to be potentially important in anoikis resistance, which was confirmed by an increase in anoikis and expression of a pro-apoptotic protein (BCL-2 like protein 4) and an apoptotic marker (cleaved poly-ADP ribose polymerase) in floating siTSG101-knockdown cells. Conclusion: To our knowledge, this is the first study that implicates the importance of TSG101 in anoikis resistance of thyroid cancer.